KUANTIFIKASI BEBERAPA PARAMETER KUALITAS GAHARU - Bambang Wiyono; Neni Sumarliani; Umi Kulsum; Evi Kusmiyati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
The draft of Indonesia National Standard for garro wood quality has a limitation where parameters used to determine the quality are still qualitative. This has caused a difficulty in assessing the quality of garro wood with different assessor. One effort to reduce this weakness is to quantify some parameters in this draft. In accordance with this, the objective of this research is to improve the draft of Indonesian National Standard for garro wood quality, so the assessment could be carried out quantitatively. The results indicated that fragrant dammar content could be quantified with resin content; weight could be quantified with specific gravity and color could be measured with chroma meter. Further analysis on the parameters showed that there were positive correlation between the quality and these examined parameters, where the increase in the garro wood quality correlated with the increase in the resin content, specific gravity and color value. This proposed draft which seems to have improvement in assessing the quality of garro wood objectively can therefore be suggested for its implementation in reducing human subjectivity.